A comparative analysis of computed tomography and ultrasonography in diagnosis of neck masses - Aqib, Mohd; Tayyaba, Zohda; Rahman, Abdur; Sharma SC; Aftab, Mohd (Asian Journal of Medical Sciences, 2023)
Background: Neck swellings constitute the chief complaint of many patients coming to ENT outpatient department. Adequate evaluation of all cases with assistance from radiological, cytopathological, and histopathological is necessary. Aims and Objectives: The present study aims to evaluate the role of clinical, radiological, and cytopathological evaluation to reach the diagnosis and the accuracy of these tools. Materials and Methods: The study was conducted in the Department of Otorhinolaryngology and Head and Neck Surgery and the Department of Radiodiagnosis, AMU, and included 100 patients with neck swelling. Results: Maximum number of patients were of lymph node masses (44%), followed by thyroid masses (26%) and salivary gland pathologies, congenital neck masses, and others. 78% were benign masses while only 22% were malignant. Out of all cases, the maximum were reactive lymphadenitis (16%), followed by metastatic lymph nodes (12%) and pleomorphic adenoma (10%). The correlation between clinical diagnosis and ultrasound (USG) was 70.93 with a diagnostic accuracy of 86%; with fine-needle aspiration cytology (FNAC) accuracy being 82%. 91% of metastatic lymph node swellings were accurately diagnosed by these two modalities alone. The sensitivity and specificity of FNAC with computed tomography (CT) were 62.25% and 98.59%, respectively; while with biopsy were 84.63% and 97.10%. Conclusion: Clinical evaluation remains the utmost important step in the management of patients with neck swellings. USG provides the necessary information to guide further management, followed by FNAC. Although CT and histopathological evaluation provide detailed information, it was rarely needed in our study to reach the clinical diagnosis however their need in the management of pathology could not be ruled out.